A low shrinkage reinforced polypropylene material and preparation method thereof

By adding peroxide and composite filler to the formula of PPGF materials and pretreatment of hydroxyacrylic emulsion, the problems of large shrinkage and direction differences in conventional PPGF materials are solved, lower shrinkage and better mechanical properties are achieved, and it is suitable for larger air conditioning blades.

CN119176988BActive Publication Date: 2025-03-04GUANGDONG SUNWILL SANTECH ENG PLASTICS DEV CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411700472.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Conventional glass fiber reinforced polypropylene material (PPGF material) has a large shrinkage rate and large shrinkage rates in different directions, resulting in small size and large jumping of injection molded air blades, which cannot meet the standard requirements at the same time.

Method used

By adding peroxide to the formula, reducing the molecular weight of polypropylene, increasing the combination of glass fiber, mica and calcium sulfate whiskers, pretreatment with hydroxyacrylic emulsion, enhancing compatibility and interface bonding, controlling the particle size and aspect ratio of the filler, forming a "secondary fill effect" to reduce the overall shrinkage rate of the material.

Benefits of technology

It significantly reduces the difference in lateral and longitudinal shrinkage rates of the material, improves the mechanical properties of the material, and meets the standard requirements of larger-sized air conditioning blades.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176988B_ABST
    Figure CN119176988B_ABST
Patent Text Reader

Abstract

The invention relates to the field of material technology, and discloses a low-shrinkage reinforced polypropylene material and a preparation method thereof. The low-shrinkage reinforced polypropylene material comprises the following raw material components calculated by mass percentage: 55-74% PP resin; 0.05-0.1% peroxide; 15-20% glass fiber; 3-6% calcium sulfate whisker; 3-6% mica; 3-8% compatibilizer; 0.5-1% hydroxy acrylic emulsion; 1-3% lubricant; 0.5-1% auxiliary agent. In the formula of the invention, the molecular weight of polypropylene is reduced by adding peroxide, so as to improve the overall shrinkage rate of the material; and by using the composite of hydroxy acrylic emulsion, mica, calcium sulfate whisker and glass fiber, utilizing the step-wise change of the aspect ratio of mica, calcium sulfate whisker and glass fiber, and using different particle size fillers for compounding, the material has a larger shrinkage rate during molding, and at the same time improves the mechanical properties of the material, which can overcome the defect of large shrinkage rate of conventional PPGF material itself.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a low-shrinkage enhanced polypropylene material and a preparation method thereof. Background Art

[0002] Polypropylene, referred to as PP, is a thermoplastic synthetic resin material with excellent performance. It has excellent overall performance and good chemical stability. It is widely used in the production of fiber products such as clothing, blankets, medical equipment, automobiles, bicycles, parts, pipelines, chemical containers, etc. However, PP materials have disadvantages such as low strength, modulus, hardness, poor low-temperature impact strength, large molding shrinkage, and easy aging. Conventional modifications to PP materials generally include strengthening and toughening, weathering modification, glass fiber reinforcement modification, flame retardant modification, and super-tough modification. Among them, glass fiber reinforced polypropylene material (referred to as PPGF material) as a new material for injection molding air conditioner fan blades has the advantages of low density, high heat resistance and excellent impact strength compared with traditional glass fiber reinforced AS material (referred to as ASGF material). However, PPGF material still has a very fatal disadvantage, that is, the shrinkage rate is large, and the shrinkage rate in different directions is very different, resulting in small size of injection molded fan blades and large runout. The height and runout of conventional PPGF material injection molded fan blades cannot meet the standard requirements at the same time.

[0003] Therefore, it is urgent to solve the above technical problems. Summary of the invention

[0004] The main purpose of the present invention is to provide a low shrinkage reinforced polypropylene material, which can overcome the defect of large shrinkage rate of conventional PPGF material itself.

[0005] To achieve the above object, the present invention provides a low shrinkage reinforced polypropylene material, which comprises the following raw material components calculated by mass percentage:

[0006] PP resin 55-74%;

[0007] Peroxide 0.05~0.1%;

[0008] Glass fiber 15-20%;

[0009] Calcium sulfate whiskers 3-6%;

[0010] Mica 3-6%;

[0011] Compatibilizer 3-8%;

[0012] Hydroxylated acrylic emulsion 0.5-1%;

[0013] Lubricant 1-3%;

[0014] Additives 0.5~1%.

[0015] The molecular weight of polypropylene is greatly reduced by adding peroxide in the formula of the present invention, so that the material can crystallize faster, greatly reducing the post-shrinkage performance of the material, thereby improving the overall shrinkage rate of the material. At the same time, through the step-wise change of the aspect ratio of glass fiber, mica and calcium sulfate whisker, different particle size fillers are used for compounding to avoid the "void effect", and a "secondary filling effect" can be formed after filling and blending, the density of the filler becomes larger, and the overall shrinkage rate is reduced. In order to better integrate the components in the formula, hydroxyl acrylic emulsion is selected to pre-treat glass fiber and mica to enhance compatibility, so that mica, glass fiber and polypropylene have a strong interface bonding degree, thereby improving the mechanical properties of the material and greatly reducing the overall shrinkage rate of the material.

[0016] Preferably, the peroxide is 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane. 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane is selected to participate in the reaction, and the decomposed free radicals thereof take hydrogen from the polypropylene molecular chain to react, resulting in polypropylene chain breakage and reorganization, greatly reducing the molecular weight of the material.

[0017] Preferably, the PP resin is high-flow polypropylene with a melt index of ≥25 g / 10min.

[0018] Preferably, the glass fiber is chopped glass fiber with a diameter of 10 to 13.5 μm and a length of 3.0 to 4.5 mm.

[0019] Preferably, the aspect ratio of the calcium sulfate whisker is 50-100, and the particle size range of the mica is 4000-5000 mesh.

[0020] Preferably, the hydroxyl content of the hydroxylated acrylic emulsion is 1 to 3%.

[0021] Preferably, the compatibilizer is maleic anhydride grafted polypropylene.

[0022] Preferably, the lubricant includes at least one of erucamide, oleamide and silicone powder.

[0023] Preferably, the auxiliary agent includes at least one of the antioxidant 1010 and the antioxidant 168 .

[0024] On the other hand, the present invention also provides a method for preparing the low shrinkage enhanced polypropylene material, comprising the following steps:

[0025] S1. Pretreatment of glass fiber and mica: Mix the hydroxy acrylic emulsion with glass fiber and mica for 3 minutes respectively, and then dry;

[0026] S2, dilute the peroxide with white oil in a ratio of 1:10;

[0027] S3, extrusion molding: PP resin, diluted peroxide, calcium sulfate whisker, pretreated mica, lubricant, compatibilizer and additives are uniformly mixed and fed from the main feed of a twin-screw extruder, and pretreated glass fiber is fed from the side feed. After melt extrusion and granulation, the extrusion temperature is controlled at 180-220° C. to obtain the low shrinkage reinforced polypropylene material.

[0028] Compared with the PPGF material in the prior art, the low-shrinkage reinforced polypropylene material prepared by the present invention has lower transverse shrinkage and longitudinal shrinkage, and various mechanical properties of the material are also significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 is a differential scanning calorimetry (DSC) curve of the PPGF material prepared in Comparative Example 2;

[0031] Figure 2 is a differential scanning calorimetry (DSC) curve diagram of the PPGF material prepared in Example 3;

[0032] Figure 3 is a differential scanning calorimetry (DSC) curve diagram of the PPGF material prepared in Example 5;

[0033] Figure 4 This is a differential scanning calorimetry (DSC) curve of the PPGF material prepared in Comparative Example 4.

[0034] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other without conflict. At the same time, the raw materials mentioned below that are not described in detail are not commercially available products; the process steps or preparation methods not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0036] The invention provides a low-shrinkage reinforced polypropylene material, which comprises the following raw material components by mass percentage: 55-74% of PP resin, 0.05-0.1% of peroxide, 15-20% of glass fiber, 3-6% of calcium sulfate whisker, 3-6% of mica, 3-8% of compatibilizer, 0.5-1% of hydroxyl acrylic emulsion, 1-3% of lubricant and 0.5-1% of auxiliary agent.

[0037] The preparation method of the above-mentioned low shrinkage enhanced polypropylene material comprises the following steps:

[0038] S1. Pretreatment of glass fiber and mica: Mix the hydroxy acrylic emulsion with glass fiber and mica for 3 minutes respectively, and then dry;

[0039] S2, dilute the peroxide with white oil in a ratio of 1:10;

[0040] S3, extrusion molding: PP resin, diluted peroxide, calcium sulfate whisker, pretreated mica, lubricant, compatibilizer and additives are uniformly mixed and fed from the main feed of a twin-screw extruder, and pretreated glass fiber is fed from the side feed. After melt extrusion and granulation, the extrusion temperature is controlled at 180-220° C. to obtain the low shrinkage reinforced polypropylene material.

[0041] In some specific embodiments, the PP resin can be selected from high-flow polypropylene with a melt index ≥ 25 g / 10 min; the peroxide can be selected from commercially available 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (bis(2,5-pentyl) vulcanizing agent).

[0042] It should be noted that among the materials used for injection molding of air conditioner blades, compared with traditional glass fiber reinforced AS materials (ASGF materials), glass fiber reinforced polypropylene materials (PPGF materials) have the advantages of extremely low density, extremely high heat resistance and excellent impact strength. The density of ASGF materials is usually 1.2 g / cm 3 , while the density of PPGF material is only 1.03 g / cm 3, applied to air conditioner blades with large volume and large weight, the total weight can be reduced by 15%, providing strong guarantee for the lightweight of air conditioner blades; the heat deformation temperature of ASGF material is only 100℃, while the heat deformation temperature of PPGF material can be as high as 150℃, the difference between the two is very large, and the heat resistance is excellent; the notched impact strength of ASGF material is only 6KJ / m 2 , and the notched impact strength of PPGF material can be as high as 12KJ / m 2 , with very excellent anti-drop performance. However, the fatal defect that prevents PPGF materials from being widely used in air-conditioning fan blades is that the shrinkage rate of PPGF materials is large, and the shrinkage rate in different directions is very different, resulting in the injection molded fan blade size being small and the jump being large. The shrinkage rate of conventional PPGF materials in the parallel flow channel direction is 0.6%, and the shrinkage rate in the vertical flow channel direction is 1.0%. The height and jump of its injection molded fan blade cannot meet the standard requirements at the same time. Therefore, in the formula of the present invention, by adding part of the peroxide dipentadienyl vulcanizer, the post-shrinkage performance of the material is significantly reduced. The free radicals decomposed by the dipentadienyl vulcanizer can capture hydrogen from the polypropylene molecular chain to react, resulting in polypropylene chain scission and recombination, thereby greatly reducing the molecular weight of polypropylene. The reduction in molecular weight causes the crystallization temperature of the material to drop significantly, allowing the material to crystallize faster in the mold cavity, greatly reducing the post-shrinkage performance of the material, thereby improving the overall shrinkage rate of the material. At the same time, there is a significant reduction in the crystallization enthalpy, and the crystallinity of the material will also decrease, thereby further reducing the shrinkage rate of the material.

[0043] In some specific embodiments, the glass fiber is PP special chopped glass fiber with a diameter of 10-13.5 μm and a length of 3.0-4.5 mm. The aspect ratio of the calcium sulfate whisker is 50-100, and the particle size of the mica is in the range of 4000-5000 mesh, preferably 5000 mesh.

[0044] It should be noted that in conventional PPGF materials, the aspect ratio of glass fiber is very large, resulting in a very large difference in shrinkage in different directions, and the product is prone to warping and deformation. The formula of the present invention adopts glass fiber, mica and calcium sulfate whisker compounding, and the ratio of glass fiber, mica and calcium sulfate whisker in the formula is regulated, and the aspect ratio and particle size range of the three are strictly screened in a suitable step range, and fillers of different particle sizes are used for compounding. The gaps between coarse particles are filled by fine particles to form the so-called "secondary filling effect", and the density of the filler becomes larger, which can not only reduce the overall shrinkage rate of the material, but also significantly shorten the shrinkage difference of the material in different directions. At the same time, the mica with a high mesh number specially selected in the present invention can play a heterogeneous nucleation effect in the material, greatly increase the crystallization rate of the material, promote the refinement of the crystal grain size, and can further reduce the shrinkage rate of the material.

[0045] In the present invention, hydroxyl acrylic emulsion is also used to pre-treat glass fiber and mica, which improves the mechanical properties of the material while reducing the overall shrinkage rate of the material. The hydroxyl acrylic emulsion is mixed with glass fiber and mica at high speed and then air-dried. Preferably, the hydroxyl content of the hydroxyl acrylic emulsion is 1-3%. Since hydroxyl acrylic emulsion, mica and glass fiber all contain a large number of hydroxyl groups, they are very compatible with each other. By controlling the hydroxyl acrylic emulsion to have a suitable molecular weight, it is easy to entangle, infiltrate and coat with mica and glass fiber. At the same time, the basic unit structure of hydroxyl acrylic emulsion is similar to that of polypropylene, and it also has good compatibility, so that there is a strong interface bonding between mica, glass fiber and polypropylene, and the three can be firmly bound together, so that the overall shrinkage rate of the material can be greatly reduced while the mechanical properties of the material can be well improved.

[0046] Specifically, the compatibilizer is commercially available maleic anhydride grafted polypropylene; the lubricant is commercially available erucamide, oleamide and silicone powder. The auxiliary agent is commercially available antioxidant 1010 and antioxidant 168.

[0047] In order to further illustrate the technical means and effects adopted by the present invention, the following is a detailed description in conjunction with specific embodiments and comparative examples.

[0048] Embodiments 1 to 5

[0049] A low shrinkage enhanced polypropylene material comprises the raw material components shown in Table 1, and the preparation method thereof comprises the following steps:

[0050] S1. Pretreatment of glass fiber and mica: Mix the hydroxy acrylic emulsion with glass fiber and mica for 3 minutes respectively, and then dry;

[0051] S2, dilute the peroxide with white oil in a ratio of 1:10;

[0052] S3, extrusion molding: PP resin, diluted peroxide, calcium sulfate whisker, pretreated mica, lubricant, compatibilizer and additives are uniformly mixed and fed from the main feed of a twin-screw extruder, and pretreated glass fiber is fed from the side feed. After melt extrusion and granulation, the extrusion temperature is controlled at 180-220° C. to obtain the low shrinkage reinforced polypropylene material.

[0053] Comparative Example 1

[0054] A low shrinkage enhanced polypropylene material comprises the raw material components shown in Table 1, and the preparation method thereof is as follows:

[0055] The PP resin, lubricant, compatibilizer and additive are uniformly mixed and fed from the main feed of a twin-screw extruder, and the glass fiber is fed from the side feed. After melt extrusion granulation, the extrusion temperature is controlled at 180-220° C. to obtain the low shrinkage reinforced polypropylene material.

[0056] Comparative Example 2

[0057] A low shrinkage enhanced polypropylene material comprises the raw material components shown in Table 1, and the preparation method thereof comprises the following steps:

[0058] S1. Pretreatment of glass fiber and mica: Mix the hydroxy acrylic emulsion with glass fiber and mica for 3 minutes respectively, and then dry;

[0059] S2, extrusion molding: PP resin, calcium sulfate whisker, pretreated mica, lubricant, compatibilizer and additives are uniformly mixed and fed from the main feed of a twin-screw extruder, and pretreated glass fiber is fed from the side feed. After melt extrusion and granulation, the extrusion temperature is controlled at 180-220° C. to obtain the low shrinkage reinforced polypropylene material.

[0060] Comparative Example 3

[0061] A low shrinkage enhanced polypropylene material comprises the raw material components shown in Table 1, and the preparation method thereof comprises the following steps:

[0062] S1. Dilute the peroxide with white oil in a ratio of 1:10;

[0063] S2, extrusion molding: PP resin, diluted peroxide, calcium sulfate whisker, mica, lubricant, compatibilizer and additives are uniformly mixed and fed from the main feed of a twin-screw extruder, and glass fiber is fed from the side feed. After melt extrusion and granulation, the extrusion temperature is controlled at 180-220° C. to obtain the low shrinkage reinforced polypropylene material.

[0064] Comparative Example 4

[0065] A low shrinkage enhanced polypropylene material comprises the raw material components shown in Table 1, and the preparation method thereof comprises the following steps:

[0066] S1. Pretreatment of glass fiber and mica: Mix the hydroxy acrylic emulsion with glass fiber and mica for 3 minutes respectively, and then dry;

[0067] S2, dilute the peroxide with white oil in a ratio of 1:10;

[0068] S3, extrusion molding: PP resin, diluted peroxide, calcium sulfate whisker, pretreated mica, lubricant, compatibilizer and additives are uniformly mixed and fed from the main feed of a twin-screw extruder, and pretreated glass fiber is fed from the side feed. After melt extrusion and granulation, the extrusion temperature is controlled at 180-220° C. to obtain the low shrinkage reinforced polypropylene material.

[0069] Table 1

[0070]

[0071] The low shrinkage reinforced polypropylene materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to performance tests, and the test methods and standards were as follows:

[0072]

[0073] The performance test results of Examples 1 to 5 and Comparative Examples 1 to 4 are shown in Table 2.

[0074] Table 2

[0075]

[0076] Referring to Table 2, from the test results of Comparative Example 1, it can be seen that the shrinkage rate of conventional PPGF materials on the market is relatively large, and the difference between the lateral and longitudinal shrinkage rates is close to 0.4%, resulting in the overall size of the injection-molded fan blades not being too large, and the difference in shrinkage rates in two different directions will cause the fan blades to warp and deform, making the fan blade's runout value far exceed the industry standard (industry standard ≤0.8, test value 1.25).

[0077] From the test results of Examples 1 to 5, it can be seen that the transverse shrinkage rate and the longitudinal shrinkage rate of the material are significantly reduced, and the difference between the transverse shrinkage rate and the longitudinal shrinkage rate is also significantly reduced. At the same time, the mechanical properties of the material are greatly increased.

[0078] Figure 1 to Figure 4 The DSC graphs of the materials are shown below when the addition amount of dipentadienyl vulcanizing agent is 0 (Comparative Example 2), 0.05% (Example 3), 0.1% (Example 5) and 0.15% (Comparative Example 4). Figure 1 As shown in Figure 2, when no dipentadienyl vulcanizing agent is added, the crystallization peak of the material is significantly higher, at 129.57°C. After adding dipentadienyl vulcanizing agent, Figure 2 As shown in the figure, the crystallization peak of the material dropped from 129.57℃ to 121.25℃, which was reduced by more than 8℃. It can be seen that the decrease in molecular weight leads to a significant decrease in the crystallization temperature of the material. When the addition amount of dipentadienyl vulcanizer is further increased to 0.15%, as shown in the figure, Figure 4As shown, its crystallization peak temperature and thermal enthalpy are increased instead. Therefore, it is shown that the content of dipentadienyl vulcanizer should not exceed 0.1%. Comparing the test results of Example 5 and Comparative Example 2, it can be seen that mica, calcium sulfate whiskers and hydroxy acrylic emulsion are added to the formula of Comparative Example 2, but dipentadienyl vulcanizer is not added, and the transverse shrinkage and longitudinal shrinkage are both high, and the difference between the two is large; the test results of Example 5 are significantly better than those of Comparative Example 2, not only the transverse shrinkage and longitudinal shrinkage are significantly reduced, but also the difference between the two is reduced. This shows that the addition of dipentadienyl vulcanizer reduces the molecular weight of the polypropylene material, thereby causing the melt index of the material to increase significantly, greatly reducing the transverse shrinkage and longitudinal shrinkage of the material.

[0079] Comparing the test results of Example 5 and Comparative Example 3, it can be seen that although the transverse shrinkage and longitudinal shrinkage of Comparative Example 3 are lower than those of Comparative Examples 1 and 2, there is still a gap with the results of Example 5, and the mechanical properties are also different. This shows that the hydroxyl acrylic emulsion can greatly improve the compatibility of polypropylene, glass fiber and mica, not only further reducing the transverse shrinkage and longitudinal shrinkage of the material, but also significantly improving the mechanical properties of the material.

[0080] By comparing the test results of Examples 2 and 5 with Comparative Example 1, it can be seen that as the content of mica and calcium sulfate whiskers gradually increases, the difference between the transverse shrinkage rate and the longitudinal shrinkage rate of the material gradually decreases, and the shrinkage rates in both directions show a significant decrease.

[0081] By comprehensively comparing Examples 1 to 5 and Comparative Examples 1 to 4, it can be concluded that the use of dipentadienyl vulcanizing agent or calcium sulfate whisker with mica or hydroxy acrylic emulsion alone cannot achieve the technical effect described in this scheme, and it is necessary to compound the four and regulate the overall effect to achieve the optimal effect described in this scheme.

[0082] In summary, the present invention adjusts the formula and adopts a compound of dipentadienyl vulcanizer, mica, calcium sulfate whisker and hydroxyl acrylic emulsion to obtain a PPGF material with not only a significantly reduced overall shrinkage rate, but also a significantly reduced difference between the lateral shrinkage rate and the longitudinal shrinkage rate. The compounding of the above formula reduces the shrinkage rate and greatly improves the various mechanical properties of the material, so that the PPGF material prepared by the present invention can be applied to larger-sized air-conditioning blades to meet industry standards.

[0083] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A low shrinkage reinforced polypropylene material, characterized in that: Calculated by mass percentage, it includes the following raw material components: PP resin 55-74%; Peroxide 0.05~0.1%; Glass fiber 15-20%; Calcium sulfate whiskers 3-6%; Mica 3-6%; Compatibilizer 3-8%; Hydroxylated acrylic emulsion 0.5-1%; Lubricant 1-3%; Additives 0.5~1%; The method for preparing the low shrinkage enhanced polypropylene material comprises the following steps: S1. Pretreatment of glass fiber and mica: Mix the hydroxy acrylic emulsion with glass fiber and mica for 3 minutes respectively, and then dry; S2, dilute the peroxide with white oil in a ratio of 1:10; S3, extrusion molding: PP resin, diluted peroxide, calcium sulfate whisker, pretreated mica, lubricant, compatibilizer and additives are uniformly mixed and fed from the main feed of a twin-screw extruder, and pretreated glass fiber is fed from the side feed. After melt extrusion and granulation, the extrusion temperature is controlled at 180-220° C. to obtain the low shrinkage reinforced polypropylene material.

2. The low shrinkage enhanced polypropylene material according to claim 1, characterized in that: The peroxide is 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.

3. The low shrinkage enhanced polypropylene material according to claim 1, characterized in that: The PP resin is selected from high-fluidity polypropylene with a melt index of ≥25 g / 10min.

4. The low shrinkage enhanced polypropylene material according to claim 1, characterized in that: The glass fibers are chopped glass fibers with a diameter of 10 to 13.5 μm and a length of 3.0 to 4.5 mm.

5. The low shrinkage enhanced polypropylene material according to claim 1, characterized in that: The aspect ratio of the calcium sulfate whisker is 50-100, and the particle size range of the mica is 4000-5000 meshes.

6. The low shrinkage enhanced polypropylene material according to claim 1, characterized in that: The hydroxyl content of the hydroxyl acrylic emulsion is 1-3%.

7. The low shrinkage enhanced polypropylene material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene.

8. The low shrinkage enhanced polypropylene material according to claim 1, characterized in that: The lubricant includes at least one of erucamide, oleamide and silicone powder.

9. The low shrinkage enhanced polypropylene material according to claim 1, characterized in that: The auxiliary agent includes at least one of the antioxidant 1010 and the antioxidant 168 .

Citation Information

Patent Citations

  • Low-shrinkage PP material for 3D printing as well as preparation method and application of low-shrinkage PP material

    CN115785566A